La construcción del suspenso en Juego de tronos. Un análisis de caso - Osorio Villanueva, Guillermo Marcelo Juan Enrique (2023)
In words of Alfred Hitchcock, suspense is the most powerful tool that a film director has in order to maintain the attention of his audience. However, the interest for the understanding of this tool is precarious if you compare it with the benefits that triggers in the audience. The aim of this article is to cover that precarious interest for its mechanisms introducing an approach for the analysis and the creation of suspense events. To achieve it, the text propose a matrix of suspense that contemplate the establishment of a moral system -whose objective is to explain why we feel empathy for beings that we do not know, knowing even that it is a fiction- and a system of probabilities that explore or enhance the dramatic tension. In order to develop it, we have analyzed four scenes of the successful TV series Game of Thrones: The Mountain and the Viper, The destruction of the Great Sept of Baelor, The death of the Night’s Watch rangers by the White Walkers, and The death of Tywin Lannister by Tyrion Lannister.